Employee Attraction : impact of employer brand image and selection process on attractiveness of potential employers - Yelemessova, Karmela (2017)
The main objective of this thesis is to investigate the impact of employer brand image and selection process on attractiveness of potential employers for their target group representatives. Author also investigated employer brand perception of a specific company among its target group representatives and proposed solutions to optimize current employee attraction strategy to better reach the target audience. Theoretical part of the thesis defines the concept of branding in general as well as that of the employer branding in particular. Practical part is dedicated to qualitative research in a form of focus groups. Main areas of research are the employer brand image perception of the specific company as well as that of a imaginary desirable employer. Author also investigated the end-to-end candidate journey to determine the main potential touchpoints between companies and their target audience. At the end of the thesis practical solutions are offered as a result of the undertaken research.